My Dear Santri, My Beloved Santri: Reflection of S.A.N.T.R.I Concept in Building Santri Identity as Rahmatan Lil 'Alamin - Syamsuhari, Syamsuhari; Thohari, M. Hamim; Pangesthi, Sambang (Green Publisher Indonesia, 2025)
The concept of S.A.N.T.R.I is a conceptual model in pesantren education that aims to develop the holistic intelligence and character of students through six main pillars, namely Scientific (science and holistic intelligence), Art (art as a path to beauty and closeness to Allah), Natural (awareness of nature and signs of Allah's greatness), Triple I (Islam, Iman, Ihsan), Result (self-evaluation and reflection), and Integrity (moral integrity and spiritual responsibility). This study uses a literature study method by examining verses of the Qur'an, Hadith, and academic references related to the value of Islamic education and pesantren traditions. The results show that the concept of S.A.N.T.R.I is able to strengthen the integration between knowledge, faith, and pious deeds, thereby giving birth to students who are not only knowledgeable but also possess noble character, love beauty, care about the environment, live based on faith values, and have high integrity, ready to become ethical agents of social change.